Association of serum D-dimer levels with disease activity in chronic urticaria, psoriasis and urticarial vasculitis - Haque, A. K. M. Reajaul; Begum, Sharmin; Islam, Tawfique R.; Shakhawat Hossain, M.; Mandal, Babu R.; Shahjahan, Fatma; Lopa, Rubaiya N.; Shyam, Nayan C. (International Journal of Research in Medical Sciences, 2026)
Background: Chronic urticaria, psoriasis and urticarial vasculitis are common skin inflammatory diseases that frequently have systemic implications. D-dimers in serum, as a coagulation activation marker, have been suggested as biomarkers for systemic inflammation in different autoimmune diseases. Its use for the evaluation of disease activity in chronic urticaria, psoriasis and urticarial vasculitis is not well established but there are no data available on the same especially in South Asian countries like Bangladesh. There is an association between serum D-dimer level and the severity of chronic urticaria, psoriasis and urticarial vasculitis, indicating its consideration as a biomarker for activity or response to therapy. Methods: A hospital-based cross-sectional study was carried out in 100 patients with chronic urticaria, psoriasis or urticarial vasculitis. The severity of the diseases was evaluated by UAS7 for chronic urticaria, PASI test in psoriasis and clinical evaluation in prematurely aged urticarial vasculitis. Serum D-dimer was detected and statistical analysis, consisting of one-way ANOVA and Pearson/Spearman correlation test, was executed. Results: The D-dimer levels were higher in all groups, the highest of which was found for the patients with urticarial vasculitis 59.7 ng/ml), whereas they were 512.4 ng/ml and 468.9 ng/ml for those with chronic urticaria and psoriasis, respectively. D-dimer levels were positively correlated with the severity of disease in all conditions to a considerable extent (p<0.001). Conclusions: Serum D-dimer level is associated with the severity of chronic urticaria, psoriasis and urticarial vasculitis, and thus may be considered as a potential biomarker for evaluating disease activity or treatment response.